Association between S. Typhi-specific memory CD4+ and CD8+ T responses in the terminal ileum mucosa and in peripheral blood elicited by the live oral typhoid vaccine Ty21a in humans - Jayaum S. Booth; Eric Goldberg; Seema A. Patil; Bruce D. Greenwald; Marcelo B. Sztein (Taylor & Francis Group, 2019)
CD4+ and CD8+ T subsets are essential components of the adaptive immune system which act in concert at the site of infections to effectively protect against pathogens. Very limited data is available in humans regarding the relationship between CD4+ and CD8+ S. Typhi responsive cells in the terminal ileum mucosa (TI) and peripheral blood following Ty21a oral typhoid immunization. Here, we compared TI lamina propria mononuclear cells (LPMC) and peripheral blood CD4+ and CD8+ T memory (TM) subsets responses and their relationship by Spearman's correlation following Ty21a immunization in volunteers undergoing routine colonoscopy. We observed that Ty21a immunization (i) influences the homing and accumulation of both CD4+ and CD8+ T cells in the TI, particularly integrin α4β7+ CCR9+ CD8+ T cells, (ii) elicits significantly higher frequencies of LPMC S. Typhi-responsive CD8+ T multifunctional (CD107a, IFNγ, IL-17A and/or MIP1β) cells than their CD4+ T counterparts, and (iii) results in the correlation of LPMC CD4+ Teffector/memory (TEM) S. Typhi responses (CD107a, IFNγ, TNFα, IL-17A and/or MIP1β) to their LPMC CD8+ TEM counterparts. Moreover, we demonstrated that these positive correlations between CD4+ and CD8+ TEM occur primarily in TI LPMC but not in PBMC, suggesting important differences in responses between the mucosal and systemic compartments following oral Ty21a immunization. This study provides the first demonstration of the correlation of S. Typhi-specific CD4+ and CD8+ TM responses in the human terminal ileum mucosa and provides valuable information regarding the generation of mucosal and systemic immune responses following oral Ty21a-immunization which might impact future vaccine design and development.